INITIATING THE IMPLEMENTATION OF BASIC PRINCIPLES OF GOOD COOPERATIVE GOVERNANCE IN THE VALUE CHAIN FINANCIAL MANAGEMENT AT THE COOPERATIVE OF FAJAR SURYA MANDIRI IN THE DISTRICT OF SIMALUNGUN - Yuni, Revita; Thohiri, Roza; Hastuti, Pebri; Silaban, Putri Sari M. J. (Journal of Community Research and Service, 2018)
AbstractThis applied research focuses on the initiative to develop a model of value chain financial management that further enabling the implementation of cooperative governance in the whole aspect of business managed by the cooperative of Fajar Surya Mandiri located at the village of Bandar Jawa, of sub-district of Bandar in the district of Simalungun at the Province of Sumatera Utara, Indonesia. More specifically, the application internal control system was introduced in cooperative business management activities that are mainly engaged with poultry and freshwater pond fish productions. The management was facilitated with the technical knowledge on the preparation of financial statements based on Financial Accounting Standard of Entities without Public Accountability as well as guiding staffs in the preparation of Standard Operating Procedure (SOP) for accounting and finance related activities and developing a website that provides profile and products of the cooperative. Applied outcomes of this community service engagement consisted of SOP and guidelines on the preparation of the financial statements of the cooperative as well as the company website and social media accounts for relevant marketing purposes.Keywords: Applied Research, Cooperative, SOP of Financial Reporting, Value Chain Financial Management, Simalungun.